2016
DOI: 10.5935/1806-0013.20160003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pain and quality of life of fibromyalgia patients

Abstract: BACKGROUND AND OBJECTIVES:It is known that fibromyalgia is a musculoskeletal syndrome characterized by chronic and widespread pain. Considering that pain has direct implications on affected patients' lives, this study aimed at evaluating pain and quality of life of fibromyalgia patients to better understand the correlation between such variables. METHODS: Cross-sectional study with 45 females aged between 30 and 55 years, in stable treatment in the month previous to selection, being excluded those under physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 22 publications
1
12
0
7
Order By: Relevance
“…The literature emphasizes that physical inactivity in FM patients is associated with loss of functionality and worsening of quality of life 4 . The reduced level of physical activity may further favor the maintenance or aggravation of the disease and some physical and physiological parameters not directly linked to the morbid process such as muscular strength and endurance, aerobic capacity and flexibility are affected over time 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature emphasizes that physical inactivity in FM patients is associated with loss of functionality and worsening of quality of life 4 . The reduced level of physical activity may further favor the maintenance or aggravation of the disease and some physical and physiological parameters not directly linked to the morbid process such as muscular strength and endurance, aerobic capacity and flexibility are affected over time 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The symptomatology of pain is a fundamental aspect to be evaluated because of its limiting character when it comes to the realization of routine and professional activities, besides being a warning sign for the search of treatment among patients. In FM patients, the main objective of interdisciplinary treatment is pain control 4 . This research showed a high percentage of women reporting intense pain, corroborating the findings of previous studies 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos realizados por Lorena et al 8 e por Martins et al 9 evidenciaram a dor da FM como um importante fator causal para redução da qualidade de vida desses pacientes. Fatores ocupacionais e o tipo de atividade física são pontos que também devem ser abordados.…”
Section: Key-wordsunclassified